Dechema chemistry data series : activity coefficients at infinite dilution 2 c10 - c36 - Tiegs, D.; Gmehling, J.; Medina, A.; Soares, M.; Bastos, J.; Alessi, P.; Kikic, I. (Frankfurt Dechema, 1986)
part 2
Keywords: coefficients -- infinite dilution